2014
DOI: 10.1016/j.bbadis.2014.04.013
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl peptidase-IV inhibition prevents blood–retinal barrier breakdown, inflammation and neuronal cell death in the retina of type 1 diabetic rats

Abstract: Diabetic retinopathy, a leading cause of vision loss in working-age population, is often associated with inflammation and apoptosis. We have previously reported that sitagliptin, a DPP-IV inhibitor, exerts beneficial effects in the retina of type 2 diabetic animals. The present study aimed to evaluate whether sitagliptin can exert protective effects in the retina of type 1 diabetic animals by a mechanism independent of insulin secretion and glycemia normalization. Streptozotocin-induced diabetic rats were trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 48 publications
3
70
0
1
Order By: Relevance
“…In addition, sitagliptin allowed for a recovery of the number of CD34 + cells present in the bloodstream to levels similar to their number in control animals, while the decreased ability of endothelial progenitor cells (EPCs) to adhere to the retinal vessels that was induced by diabetes was reversed. Even more interestingly, the same authors demonstrated that sitagliptin alleviated the increased BRB permeability in streptozotocin (STZ)-induced diabetic rats, which could not be attributed to a normalisation of glycaemia [31]. However, Lee et al [32] recently reported that the intraperitoneal administration of sitagliptin induced vascular leakage in the retinas of mice with either retinopathy of prematurity or STZ-induced diabetes.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, sitagliptin allowed for a recovery of the number of CD34 + cells present in the bloodstream to levels similar to their number in control animals, while the decreased ability of endothelial progenitor cells (EPCs) to adhere to the retinal vessels that was induced by diabetes was reversed. Even more interestingly, the same authors demonstrated that sitagliptin alleviated the increased BRB permeability in streptozotocin (STZ)-induced diabetic rats, which could not be attributed to a normalisation of glycaemia [31]. However, Lee et al [32] recently reported that the intraperitoneal administration of sitagliptin induced vascular leakage in the retinas of mice with either retinopathy of prematurity or STZ-induced diabetes.…”
Section: Discussionmentioning
confidence: 98%
“…The experimental evidence on the effects of the oral administration of DPP-IVi in diabetic retinopathy is limited and controversial [29][30][31][32]. Gonçalves et al [29] showed that sitagliptin prevented changes in the endothelial distribution of tight junction proteins and decreased nitrosative stress, the inflammatory state and cell death by apoptosis in Zucker Diabetic Fatty (ZDF) rats (a rat model of type 2 diabetes).…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diabetes mellitus and/or arterial hypertension, this reflex arc is impaired, most probably caused by deterioration in the release and metabolism of nitric oxide [15][16][17][18]. Beneficial effects of DPP-IV inhibition on blood pressure, retinal and renal function have been suggested in experimental studies [19][20][21] and in individuals with type 2 diabetes mellitus [10,11,22,23]. In our study, treatment with linagliptin improved retinal capillary perfusion, retinal arterial blood flow and the hyperemic response to flicker light in nondiabetic, hypertensive individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Maeda et al (104) showed that vildagliptin significantly increased retinal gene expression of vascular endothelial growth factor, intercellular adhesion molecule 1, plasminogen activator inhibitor 1, and pigment epithelium-derived factor. Gonçalves et al (105) have also shown that in the retina of STZ-induced T1D rats, sitagliptin prevented the increase in blood-retinal barrier permeability and inhibited the changes in immunoreactivity and endothelial subcellular distribution of occludin, claudin 5, and zonula occludens 1 proteins induced by diabetes. Furthermore, sitagliptin decreased the retinal inflammatory state and neuronal apoptosis, thus indicating a direct protective effect on diabetic retinal cells.…”
Section: Dpp4-i and Diabetic Retinopathymentioning
confidence: 92%